A method for improving the creep resistance of high-temperature titanium-based composite materials by cyclic heat treatment

Through the cyclic heat treatment process, silicide and nanotwins are introduced, which solves the problem of insufficient creep resistance performance of high-temperature titanium-based composite materials, and has achieved significant improvement in the material's performance. It is suitable for high-demand aerospace applications such as supersonic vehicles.

CN118222862BActive Publication Date: 2025-04-25HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410343575.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-25
Publication Date
2025-04-25
Estimated Expiration
2044-03-25

AI Technical Summary

Technical Problem

The creep resistance performance of existing high-temperature titanium-based composite materials cannot be effectively improved, especially in supersonic aircraft applications, where the strength, plasticity and creep resistance of the material are insufficient.

Method used

The cyclic heat treatment process is adopted to improve the creep resistance of the material by introducing and regulating silicides and nanotwins. Specific steps include: determining the appropriate matrix alloy composition, performing vacuum induction smelting and casting, and then introducing high thermal stress and dislocation substructures through cyclic heat treatment to regulate the formation of silicides and nanotwins.

Benefits of technology

It significantly improves the creep resistance of high-temperature titanium-based composites, increases the creep life by 100%, and reduces the steady-state creep rate by an order of magnitude, and is suitable for aerospace applications with complex structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118222862B_ABST
    Figure CN118222862B_ABST
Patent Text Reader

Abstract

A method for improving the creep resistance of high-temperature titanium-based composite materials by cyclic heat treatment, the present invention relates to the field of titanium-based composite materials. The present invention is to solve the technical problem that the existing strengthening means of high-temperature titanium-based composite materials cannot effectively improve the creep resistance. The specific steps are: 1. Weighing raw materials according to the determined components; 2. Preparing a high-temperature titanium-based composite material ingot; 3. Performing cyclic heat treatment on the ingot. The rod-shaped S1-type silicide obtained by the present invention has a size of 10 to 200 nm and is distributed inside the α layer and at the α / β interface. The nanotwins obtained by the present invention have a thickness of 20 to 50 nm, are distributed inside the α layer, and are perpendicular to the α / β interface. By controlling the time, temperature, number of cycles, and cooling rate of the cyclic heat treatment, the characteristic parameters of the silicide and the nanotwins can be regulated, thereby meeting the performance requirements of complex aviation structural parts. The high-temperature titanium-based composite material of the present invention is used in the field of aerospace.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of titanium-based composite materials. Background Art

[0002] High-temperature titanium alloys have the advantages of low density, high strength, and excellent high-temperature performance, and have been widely used in aviation structural parts such as compressor blades and discs. On this basis, high-temperature titanium-based composite materials prepared by introducing ceramic particles and rare earth oxides with high-temperature titanium alloy as the matrix alloy combine the ductility and toughness of the titanium matrix with the high strength and high modulus of ceramics, and have good application potential in the aviation field.

[0003] When the hot end parts of aircraft are working, they will be subjected to complex effects such as high temperature, complex stress, and airflow erosion. Creep deformation will inevitably occur under long-term service. Therefore, creep resistance is an important indicator to measure the service reliability of high-temperature titanium-based composite materials. The continuous development of supersonic aircraft has put forward higher requirements on the strength, plasticity, and especially creep resistance of high-temperature titanium-based composite materials. At present, the conventional strengthening methods of high-temperature titanium-based composite materials are concentrated on severe plastic deformation processes represented by forging and rolling. These methods have complex processes, high costs, and are not suitable for castings with complex configurations. In addition, for high-temperature titanium-based composite materials, the deformation of the reinforcing phase and the matrix during forging and rolling is often uncoordinated, which leads to a large amount of debonding or fracture of the reinforcing phase during the deformation process, significantly reducing the plasticity of the material. Summary of the invention

[0004] In order to solve the technical problem that the existing strengthening means of high-temperature titanium-based composite materials cannot effectively improve the creep resistance, the present invention provides a method for improving the creep resistance of high-temperature titanium-based composite materials by cyclic heat treatment.

[0005] The present invention provides a cyclic heat treatment process, which improves creep resistance by introducing and regulating silicides and nano twins. The silicides come from the local internal stress and dislocation substructure introduced by the cyclic heat treatment. Compared with the spherical (Ti, Zr) precipitated by the common solution aging heat treatment 6 Si 3 Compared with the S2 type silicide, this large amount of rod-shaped (Ti, Zr) 5 Si 3 -S1 type silicide has a stronger pinning effect on dislocation movement. Different from common growth twins, annealing twins, and deformation twins, the nano twins introduced in this process come from the difference in variant selection during the phase transition from high-temperature β phase to low-temperature α phase. This new method for regulating silicide and nano twins is easy to operate and has important significance for the application of high-temperature titanium-based composites in aerospace and other fields.

[0006] A method for improving the creep resistance of high-temperature titanium-based composite materials by cyclic heat treatment, which is specifically carried out in the following steps:

[0007] 1. According to the weight percentage: Al is 5% to 10%, Sn is 1% to 5%, Zr is 1% to 8%, Mo is 0.4% to 2%, W is 1% to 2%, Nb is 1% to 2%, Si is 0.1% to 0.6% and the balance is Ti, and the total volume percentage of the reinforcing phase TiB and TiC in the high-temperature titanium-based composite material is 1% to 5% and Y 2 O 3 The raw materials are weighed with a volume percentage of 0.1% to 0.5%, and the raw materials include sponge titanium, titanium rod, high-purity aluminum, sponge zirconium, high-purity tin, high-purity silicon, aluminum-molybdenum master alloy, aluminum-tungsten master alloy, aluminum-niobium master alloy, B 4 C powder, C powder and nano Y 2 O 3 pink;

[0008] 2. Wrap the powder raw material weighed in step 1 with aluminum foil and put it into the secondary feeding hopper; put the remaining raw materials into a water-cooled copper crucible, evacuate it, and then fill it with protective gas to heat it; when the raw materials in the crucible are completely melted to form a melt, add the powder raw materials in the secondary feeding hopper into the melt, increase the heating power, control the melting temperature to 1550°C to 1650°C, and stir the melt electromagnetically; then pour the melt into a preheated steel mold, and obtain a high-temperature titanium-based composite material ingot after cooling;

[0009] 3. Cyclic heat treatment: placing the high-temperature titanium-based composite material ingot obtained in step 2 into a heat treatment furnace, setting the heat treatment temperature to 550-650°C, and keeping the temperature for 5-10 hours after the furnace temperature of the heat treatment furnace reaches the target temperature, and then cooling to room temperature to complete a heat treatment;

[0010] The cooled ingot is then subjected to repeated heat treatment process 20 to 50 times to complete.

[0011] The matrix alloy composition determined in step 1 of the present invention is based on the mature Ti-Al-Sn-Zr-Mo-W-Nb-Si system in the near-α-type high-temperature titanium alloy, and the maximum use temperature of this alloy can be close to 600°C. Compared with the commonly used high-temperature titanium alloys such as IMI834, Ti1100, and Ti60, the present invention adopts higher contents of Al, Mo, Nb, W, and Si elements. Specifically, the addition of Al element is conducive to reducing the stacking fault energy of the titanium matrix and increasing the possibility of nano twin formation. The formation of nano twins in the present invention comes from the β→α phase transition process, so a higher content of three β-stabilizing elements Mo, Nb, and W are added to the matrix alloy. On the one hand, the addition of trace β-stabilizing elements can effectively improve the instantaneous strength, and on the other hand, an appropriate amount of β phase can create favorable conditions for the formation of nano twins and silicides. In general, the silicides precipitated by heat treatment are concentrated around the α / β interface and have a significant distribution tendency; while the silicides after heat treatment in the present invention can be dispersed and distributed inside the α layer, which has little effect on the plasticity of the material, so the amount of Si added is increased.

[0012] In the second step of the present invention, TiB and TiC reinforcement phases are generated in situ during the casting process. The two reinforcement phases have a similar thermal expansion coefficient to the titanium matrix, and the total amount is limited to 1% to 5% to prevent the addition of excessive reinforcement phases from significantly deteriorating the plasticity. In addition, Y 2 O 3 Reinforcement phase, excessive nanopowder is easy to cause agglomeration, unable to achieve uniform distribution of reinforcement phase and thus reduce the mechanical properties of the material. 2 O 3 The amount of reinforcement phase added is limited to 0.1% to 0.5%.

[0013] In step three of the present invention, high thermal stress and high-density dislocation substructures are introduced into the high-temperature titanium-based composite material based on the difference in thermal expansion coefficients between each component and the titanium matrix during the cooling process through multiple cycles of heat treatment; further, the characteristic regulation of silicide and nanotwins can be achieved respectively by adjusting the cyclic heat treatment parameters. The specific regulation method is: ① For silicide, its characteristic parameters depend on the heat treatment temperature and time. In the early stage of heat treatment, silicide is mainly precipitated at the α / β interface; and as the number of cycles increases, the nucleation energy of silicide at the introduced high-density dislocation is low, and then a large amount of silicide is precipitated inside the grain. On the other hand, there are significant differences in the precipitation behavior of silicide at different heat treatment temperatures. When the heat treatment temperature is low (about 550°C), the precipitation of silicide is very limited, and the characteristic parameters are not sensitive to the heat treatment time; and when the heat treatment temperature exceeds 600°C, the silicide will be significantly coarsened with the increase of temperature. ② For nanotwins, the formation mechanism of twins is the difference in variant selection of the α / β phase transformation during the heat treatment cooling process. Therefore, the single heat treatment time has little effect on nanotwins, and its characteristic parameters mainly depend on the heat treatment temperature and cooling method. The higher the heat treatment temperature and the faster the cooling method, the higher the possibility that the relatively high-energy variant II grain boundary will transform into a more energetically stable twin boundary during the cooling process, and the more intense the precipitation of nanotwins. The more times of cyclic heat treatment and the more frequent the cooling process, the greater the number of nanotwins; as the total time of cyclic heat treatment increases, the precipitated nanotwins can grow fully and the size of the twins gradually increases.

[0014] Beneficial effects of the present invention:

[0015] The invention adopts a heat treatment process with simple operation to realize a significant improvement in creep resistance, and is suitable for high-temperature titanium-based composite material castings with complex structures.

[0016] (1) The present invention can achieve the separate regulation of silicide and nanotwins by designing and adjusting the heat treatment temperature, time, number of cycles, and cooling method. Compared with the existing reports, the present invention is different in that: 1. In addition to the spherical S2 silicide commonly seen in solution aging heat treatment, a large amount of rod-shaped S1 silicide is precipitated inside the grains, and the latter has a stronger pinning effect on dislocations; 2. Through the difference in variant selection of α / β phase transformation during cooling, based on a new formation mechanism, a large number of stable nanotwins are introduced into the titanium matrix without severe deformation.

[0017] (2) The silicide and nano twins of the present invention make the high temperature titanium-based composite material have excellent creep resistance. Compared with the cast state, the creep life after cyclic heat treatment can be increased by 100%, and the steady-state creep rate can be reduced by one order of magnitude.

[0018] (3) The preparation process involved in the present invention includes vacuum induction melting and a cyclic heat treatment process matched with a high-temperature titanium-based composite material. The process is simple and has a wide range of applications. It can meet the performance requirements of complex aviation structural parts and can be extended to other metal materials that follow variant selection during heat treatment cooling.

[0019] In summary, the present invention introduces a large amount of diffusely distributed silicides and nanotwins into the titanium matrix based on the high thermal stress in the cyclic heat treatment. The size of the rod-shaped S1-type silicide obtained by the present invention is 10 to 200 nm, and is distributed inside the α layer and at the α / β interface. The thickness of the nanotwins obtained by the present invention is 20 to 50 nm, distributed inside the α layer, and perpendicular to the α / β interface. By controlling the time, temperature, number of cycles, and cooling rate of the cyclic heat treatment, the characteristic parameters of the silicide and nanotwins can be controlled, thereby meeting the performance requirements of complex aviation structures.

[0020] The high-temperature titanium-based composite material of the invention is used in the field of aerospace. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The morphology of the silicide precipitated in the high-temperature titanium-based composite material after cyclic heat treatment in Example 1; wherein (b) is a partial enlarged view of (a);

[0022] Figure 2 The morphology of nano twins precipitated in the high-temperature titanium-based composite material after cyclic heat treatment in Example 1; Figure (a) and Figure (b) are different positions of the high-temperature titanium-based composite material;

[0023] Figure 3 This is a creep curve of the high-temperature titanium-based composite material after cyclic heat treatment in Example 1 under the conditions of 650°C / 230MPa. DETAILED DESCRIPTION

[0024] Specific implementation method 1: This implementation method is a method for improving the creep resistance of high-temperature titanium-based composite materials by cyclic heat treatment, which is specifically carried out in the following steps:

[0025] 1. According to the weight percentage: Al is 5% to 10%, Sn is 1% to 5%, Zr is 1% to 8%, Mo is 0.4% to 2%, W is 1% to 2%, Nb is 1% to 2%, Si is 0.1% to 0.6% and the balance is Ti, and the total volume percentage of the reinforcing phase TiB and TiC in the high-temperature titanium-based composite material is 1% to 5% and Y 2 O 3 The raw materials are weighed with a volume percentage of 0.1% to 0.5%, and the raw materials include sponge titanium, titanium rod, high-purity aluminum, sponge zirconium, high-purity tin, high-purity silicon, aluminum-molybdenum master alloy, aluminum-tungsten master alloy, aluminum-niobium master alloy, B4 C powder, C powder and nano Y 2 O 3 pink;

[0026] 2. Wrap the powder raw material weighed in step 1 with aluminum foil and put it into the secondary feeding hopper; put the remaining raw materials into a water-cooled copper crucible, evacuate it, and then fill it with protective gas to heat it; when the raw materials in the crucible are completely melted to form a melt, add the powder raw materials in the secondary feeding hopper into the melt, increase the heating power, control the melting temperature to 1550°C to 1650°C, and stir the melt electromagnetically; then pour the melt into a preheated steel mold, and obtain a high-temperature titanium-based composite material ingot after cooling;

[0027] 3. Cyclic heat treatment: placing the high-temperature titanium-based composite material ingot obtained in step 2 into a heat treatment furnace, setting the heat treatment temperature to 550-650°C, and keeping the temperature for 5-10 hours after the furnace temperature of the heat treatment furnace reaches the target temperature, and then cooling to room temperature to complete a heat treatment;

[0028] The cooled ingot is then subjected to repeated heat treatment process 20 to 50 times to complete.

[0029] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: in step 1, the mass purity of titanium sponge is greater than 99%, the mass purity of titanium rod is greater than 99%, the mass purity of high-purity aluminum is greater than 99%, the mass purity of zirconium sponge is greater than 99%, the mass purity of high-purity tin is greater than 99%, and the mass purity of high-purity silicon is greater than 99%. Other aspects are the same as specific implementation method 1.

[0030] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: in step 1, the content of Mo in the aluminum-molybdenum master alloy is 50.5wt.%, the content of W in the aluminum-tungsten master alloy is 57.44wt.%, and the content of Nb in the aluminum-niobium master alloy is 83.15wt.%. The rest is the same as specific implementation method 1 or 2.

[0031] Specific implementation method 4: This implementation method is different from specific implementation methods 1 to 3 in that: when weighing raw materials in step 1, the mass of Al element is increased by 2% to 4%, and the mass of Sn element is increased by 5% to 8% to compensate for the burning loss. The rest is the same as specific implementation methods 1 to 3.

[0032] Specific implementation method 5: This implementation method is different from the specific implementation methods 1 to 4 in that: the powder raw material in step 2 includes B 4 C powder, C powder and nano Y 2 O 3 The rest is the same as that of the first to fourth embodiments.

[0033] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that the vacuum is evacuated to below 5 Pa in step 2. The rest is the same as specific implementation methods 1 to 5.

[0034] Specific implementation method 7: This implementation method is different from specific implementation methods 1 to 6 in that argon gas is filled as protective gas in step 2. The rest is the same as specific implementation methods 1 to 6.

[0035] Specific implementation eight: This implementation differs from specific implementations one to seven in that the electromagnetic stirring time in step two is 5 to 10 minutes. The rest is the same as specific implementations one to seven.

[0036] Specific implementation method 9: This implementation method is different from specific implementation methods 1 to 8 in that the cooling in step 3 is furnace cooling or air cooling. The rest is the same as specific implementation methods 1 to 8.

[0037] Specific implementation 10: This implementation is different from specific implementations 1 to 9 in that the total cumulative heat treatment time in step 3 is controlled to be 100 to 500 hours. The rest is the same as specific implementations 1 to 9.

[0038] The content of the present invention is not limited to the content of the above-mentioned embodiments. The combination of one or several specific embodiments can also achieve the purpose of the invention.

[0039] Embodiment 1:

[0040] This embodiment provides a method for improving the creep resistance of a high-temperature titanium-based composite material by cyclic heat treatment, which is specifically carried out in the following steps:

[0041] 1. According to the weight percentage: Al is 6%, Sn is 4%, Zr is 8%, Mo is 0.8%, W is 1%, Nb is 1%, Si is 0.25% and the balance is Ti, and the volume percentage of the reinforcing phase TiB in the high-temperature titanium-based composite material is 2%, the volume percentage of TiC is 2% and Y 2 O 3 Weigh the raw materials with a volume percentage of 0.3%, and Y 2 O 3 The raw materials are weighed with a volume percentage of 0.3%, including sponge titanium, titanium rod, high-purity aluminum, sponge zirconium, high-purity tin, high-purity silicon, aluminum-molybdenum master alloy, aluminum-tungsten master alloy, aluminum-niobium master alloy, B 4 C powder, C powder and nano Y 2 O 3 pink;

[0042] 2. The powder raw material (B 4 C powder, C powder and nano Y 2 O3 The powder (powder) is wrapped with aluminum foil and placed in a secondary feeding hopper; the remaining raw materials are placed in a water-cooled copper crucible, evacuated to below 5 Pa, and then filled with argon as a protective atmosphere for heating; when the raw materials in the crucible are completely melted to form a melt, the powder raw materials in the secondary feeding hopper are added to the melt, the heating power is increased to 90KW, the melting temperature is controlled to reach 1600°C, and the melt is electromagnetically stirred for 8 minutes, and the electromagnetic stirring speed is 1000rpm; then the melt is poured into a preheated steel mold, and a high-temperature titanium-based composite material (TMC) ingot is obtained after cooling; the reinforcing phase content in the high-temperature titanium-based composite material ingot is 2Vol.%TiB+2Vol.%TiC+0.3Vol.%Y 2 O 3 ;

[0043] 3. Cyclic heat treatment: the high-temperature titanium-based composite material ingot obtained in step 2 is placed in a heat treatment furnace, the heat treatment temperature is set to 650°C, and when the furnace temperature of the heat treatment furnace reaches the target temperature, it is kept warm for 10 hours, and then cooled to room temperature, thus completing a heat treatment;

[0044] The cooled ingot was then subjected to repeated heat treatment for 20 times, with a total cumulative heat treatment time of 200 h, and the high-temperature titanium-based composite material (TMC-HT) was obtained.

[0045] Figure 1 The morphology of silicides precipitated from the high-temperature titanium-based composite material after cyclic heat treatment in Example 1. As can be seen from the figure, a large number of dislocations and rod-shaped S1 silicides based on dislocation distribution are observed inside the α layer. The size of these silicides is nanometer-scale, with multiple orientations and dispersed distribution.

[0046] Figure 2 This is a morphology of nano twins precipitated in the high temperature titanium-based composite material after cyclic heat treatment in Example 1. It can be seen that a large number of nano twins are precipitated perpendicular to the α / β interface, the thickness of these twins is 20-30nm, and a small amount of silicide is precipitated around the twins.

[0047] Figure 3 The creep curve of the high-temperature titanium-based composite material after cyclic heat treatment at 650°C / 230MPa in Example 1 is shown in the figure. As can be seen from the figure, thanks to the precipitation of silicide and nano twins, the creep life of the material after cyclic heat treatment is increased by 108%, and the steady-state creep rate is reduced by 50%, showing an excellent strengthening effect.

Claims

1. A method for improving the creep resistance of high-temperature titanium-based composite materials by cyclic heat treatment, characterized in that The method is specifically carried out in the following steps:

1. Weigh raw materials according to the weight percentage: Al is 5% to 10%, Sn is 1% to 5%, Zr is 1% to 8%, Mo is 0.4% to 2%, W is 1% to 2%, Nb is 1% to 2%, Si is 0.1% to 0.6% and the balance is Ti, and the total volume percentage of the reinforcing phase TiB and TiC in the high-temperature titanium-based composite material is 1% to 5% and the volume percentage of Y2O3 is 0.1% to 0.5%. The raw materials include sponge titanium, titanium rods, high-purity aluminum, sponge zirconium, high-purity tin, high-purity silicon, aluminum-molybdenum master alloy, aluminum-tungsten master alloy, aluminum-niobium master alloy, B4C powder, C powder and nano Y2O3 powder; 2. Wrap the powder raw material weighed in step 1 with aluminum foil and put it into the secondary feeding hopper; put the remaining raw materials into a water-cooled copper crucible, evacuate it, and then fill it with protective gas to heat it; when the raw materials in the crucible are completely melted to form a melt, add the powder raw materials in the secondary feeding hopper into the melt, increase the heating power, control the melting temperature to 1550°C to 1650°C, and stir the melt electromagnetically; then pour the melt into a preheated steel mold, and obtain a high-temperature titanium-based composite material ingot after cooling; 3. Cyclic heat treatment: placing the high-temperature titanium-based composite material ingot obtained in step 2 into a heat treatment furnace, setting the heat treatment temperature to 550-650°C, and keeping the temperature for 5-10 hours after the furnace temperature of the heat treatment furnace reaches the target temperature, and then cooling to room temperature to complete a heat treatment; The cooled ingot is then subjected to repeated heat treatment process 20 to 50 times to complete; In step 3, the total cumulative heat treatment time is controlled to be 100 to 500 hours; The cooling in step 3 is furnace cooling or air cooling.

2. The method for improving the creep resistance of high-temperature titanium-based composite materials by cyclic heat treatment according to claim 1, characterized in that The mass purity of the titanium sponge described in step 1 is >99%, the mass purity of the titanium rod is >99%, the mass purity of the high-purity aluminum is >99%, the mass purity of the zirconium sponge is >99%, the mass purity of the high-purity tin is >99%, and the mass purity of the high-purity silicon is >99%.

3. The method for improving the creep resistance of high-temperature titanium-based composite materials by cyclic heat treatment according to claim 1, characterized in that In step 1, the Mo content in the aluminum-molybdenum master alloy is 50.5wt.%, the W content in the aluminum-tungsten master alloy is 57.44wt.%, and the Nb content in the aluminum-niobium master alloy is 83.15wt.%.

4. The method of improving the creep resistance of high-temperature titanium-based composite materials by cyclic heat treatment according to claim 1, characterized in that Step 1: When weighing the raw materials, the mass of the Al element is increased by 2% to 4%, and the mass of the Sn element is increased by 5% to 8% to compensate for the burn loss.

5. The method of improving the creep resistance of high-temperature titanium-based composite materials by cyclic heat treatment according to claim 1, characterized in that The powder raw materials in step 2 include B4C powder, C powder and nano Y2O3 powder.

6. The method of improving the creep resistance of high-temperature titanium-based composite materials by cyclic heat treatment according to claim 1, characterized in that In step 2, the pressure is evacuated to below 5 Pa.

7. The method of improving the creep resistance of high-temperature titanium-based composite materials by cyclic heat treatment according to claim 1, characterized in that In step 2, argon is filled as a protective gas.

8. The method of improving the creep resistance of high-temperature titanium-based composite materials by cyclic heat treatment according to claim 1, characterized in that The electromagnetic stirring time in step 2 is 5 to 10 minutes.

Citation Information

Patent Citations

  • Preparation method of multi-element reinforced high-temperature titanium-based composite material

    CN113388756A

  • Electromagnetic cold crucible circulating heat treatment system and method for refining titanium-aluminum alloy structure through circulating heat treatment

    CN114959526A